The Voice of the Qur'an's Potential in Pain Management : Review Study - Purnawan, Iwan; Widyastuti, Yunita; Setiyarini, Sri; Probosuseno, P (Universitas Muhammadiyah Surakarta, 2022)
Pain is multidimensional. Pharmacological therapy is still not optimal and has unwanted side effects. Therefore, a safe, effective, and comprehensive non-pharmacological therapy is needed to compensate for the lack of pharmacological therapy. Listening to the recitation of the Quran in several studies has been shown to have a relaxing effect in various situations. The study aims to see whether listening to the Quran as a type of non-pharmacological therapy will help people overcome pain. Method used is comprehensive search on multiple databases (Clinical Key, Cochrane Lab, Medline, Host EBSCO, ProQuest, Science Direct, and Springer Link) using the term